1987
DOI: 10.1093/ageing/16.5.311
|View full text |Cite
|
Sign up to set email alerts
|

A Sero-Epidemiological Study of Conventional Infectious Agents in Alzheimer's Disease

Abstract: Serum antibody titres to Adenovirus, Chlamydia Group B, Coxiella burnettii, Cytomegalovirus, Herpes simplex virus, Influenza A, Influenza B, Measles and Mycoplasma pneumoniae were measured in 33 patients with a clinical diagnosis of Alzheimer's disease, and in 28 non-demented controls suffering from functional psychiatric disorders. No statistically significant differences were found between the patients and controls, and it is concluded that these agents play no role in the aetiology of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…In our study, however, no elevated titer of antibodies to HSV-1 was noted in sera from AD patients, in contrast to the results found in the control subjects, which could reflect a possible reactivation of the virus (50,61). The similar anti-CMV antibody titers observed in the AD and control groups confirmed the observations made by Whalley et al (62) and Renvoize et al (63,64), who also found no increased prevalence of anti-CMV antibodies in the sera of demented patients. However, our results indicate that anti-CMV antibodies are more frequently found in control subjects, as recently reported by McVoy and Adler (65).…”
supporting
confidence: 90%
“…In our study, however, no elevated titer of antibodies to HSV-1 was noted in sera from AD patients, in contrast to the results found in the control subjects, which could reflect a possible reactivation of the virus (50,61). The similar anti-CMV antibody titers observed in the AD and control groups confirmed the observations made by Whalley et al (62) and Renvoize et al (63,64), who also found no increased prevalence of anti-CMV antibodies in the sera of demented patients. However, our results indicate that anti-CMV antibodies are more frequently found in control subjects, as recently reported by McVoy and Adler (65).…”
supporting
confidence: 90%
“…15 In contrast, 1 study including 33 Alzheimer patients and 28 nondemented controls found no differences in seropositivity toward common infectious agents (HSV, CMV, and influenza) between cases and controls. 16 Of various bacteria, Chlamydia pneumonia 17 in particular and also Mycoplasma pneumoniae 18 have been associated with the pathogenesis of atherosclerotic vascular diseases. These associations are potentially interesting for cognitive disorders because late-onset dementia, including Alzheimer disease, is increasingly considered a vascular disorder.…”
mentioning
confidence: 99%
“…However many studies have failed to demonstrate the presence of viral or pathogen DNA in Alzheimer's disease sera (a problem common to many viral-related diseases) e.g. 61,62 . If however, the pathogen has already invoked an antibody response, that also targets its human homologues, the immune response will become self-sustaining as antibodies continue to encounter the human proteins, even if the virus has been successfully eliminated.…”
Section: On the Absence Of Viral Dnamentioning
confidence: 99%